Success Factors for Open-Source Software Development from Vendor’s Perspective: An Empirical Study: Success Factors for OSSD - Haider, Shehzad; Khalil, Wajeeha; Rashid, Nasir; Khalid, Shah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Open-Source Software (OSS) development is an innovative paradigm to develop software by exploring unique solutions, acquiring the tacit programming knowledge of experts and to make the code freely available for reuse and improvement. OSS effectively delivers automation through a rich collaboration of geographically distributed experts with common goals and interests. OSS, being highly recognized in the software community is coined as futuristic model to meet ever the tremendous changes in requirements with high level of flexibility. Due to the increased positive economic impact, OSS is now globally adapted to deliver remarkable software with increased productivity. The principal aim of this research is to probe the state-of-art success factors in adapting OSS by conducting systematic literature review (SLR). To address the research questions, 159 studies were systematically analyzed, which resulted in 17 success factors. Out of the total list of identified success factors, four were pinpointed as significant, bearing high frequency. The significant success factors are “source code availability,” “Low development cost,” “High quality end product” and “Identification and fixing of bugs with ease”. In addition, the results from SLR were validated through an online survey from relevant OSS experts globally. The findings of the questionnaire survey are mostly consistent with SLR results. The identified results provide insights to the software community in general and OSS developers in specific the propound success factors for adapting the OSS.